(untitled) (Western Journal of Medical and Biomedical Sciences, 2024)
Neoplasms of the spine can be primary or secondary (metastatic), they are relatively rare and occur in individuals of all ages. Their clinical manifestations include back pain, motor/sensory deficits and loss of sphincter function. These tumours can affect every region of the spine and can be intradural or extradural. This study analysed the age, sex, clinical presentation, anatomic distribution and histopathological pattern of neoplasms of the spine diagnosed histologically at the Jos University Teaching Hospital between the 1st of January 2012 and 31st December 2022. This retrospective observational studywas carried out in Jos, Plateau state, North-central Nigeria. The study utilised patient hard copy case-files, electronic histopathology result records, electronic cancer registry entries and histopathology glass slides. The data obtained was analysed using Epi-info 7 (version 3.5.4) and Microsoft-Excel and presented in tables and figures. Approximately 2.4 cases ofneoplasms of the spine were diagnosed per year over the 11 years of ourreview. Primaryneoplasms were 61.5%(16) of cases and secondary neoplasms 38.5%(10). Patient ages ranged from 10 to 72 years (mean age of 42.3±16 years). There were 17 males and 9 females (M:F= 1.8:1). The commonest presenting symptoms were motor deficit (84.6%, 22) and back pain (76.9%, 20). The thoracic spine (57.7%, 15) was the commonest spinal region affected and the extradural location 53.8%(14) of cases the most frequent. In conclusion, the age and sex distribution, clinical presentation, anatomical localisation and histopathological pattern of neoplasms of the spine seen in our study is fairly consistent with published literature. We recommend improved neurosurgical and histopathological assessment and characterisation of secondary neoplasms of the spine.